2019
DOI: 10.1097/pcc.0000000000001862
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Ventilator Care Bundle to Prevent Ventilator-Associated Pneumonia at the PICU: A Systematic Review and Meta-Analysis

Abstract: Objectives: Ventilator-associated pneumonia is one of the most frequent hospital-acquired infections in mechanically ventilated children. We reviewed the literature on the effectiveness of ventilator care bundles in critically ill children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
1
25
1
Order By: Relevance
“…AEs, such as hospital‐acquired infections, have been shown to decrease when evidence‐based guidelines such as, ventilator‐associated pneumonia prevention guideline, are followed 29‐32 . In addition, the frequencies of infections were found to decrease substantially depending on the design of the ICU and by caring for intensive care patients in single‐patient rooms rather than multibed rooms 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…AEs, such as hospital‐acquired infections, have been shown to decrease when evidence‐based guidelines such as, ventilator‐associated pneumonia prevention guideline, are followed 29‐32 . In addition, the frequencies of infections were found to decrease substantially depending on the design of the ICU and by caring for intensive care patients in single‐patient rooms rather than multibed rooms 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, the clinical diagnosis of VAP is mainly based on clinical symptoms and signs, lung imaging, and sputum bacteriological test, which, however, have low specificity and cannot accurately determine bacterial, fungal, and viral infections. Moreover, the bacteriological test lasts for a long time, delaying the treatment (9). It was found in previous clinical practice that PCT can be used to diagnose early potential infection in patients with VAP more accurately (10).…”
Section: Discussionmentioning
confidence: 99%
“…This is also confirmed to a certain extent by the findings of Matics et al and Lalitha et al found that when pSOFA score was more than 8 on both days 1 and 3, the relative risk of prolonged duration of mechanical ventilation was increased ( 21 ). When the initial pSOFA score at the beginning of ventilator use is ≥8, the risk of mechanical ventilation duration ≥96 h is higher, so taking effective preventive measures in nursing and treatment can improve patient outcomes ( 22 ). For children with a score >8, chest radiographs should be performed 72 h after mechanical ventilation, so that VAP can be detected and treated early.…”
Section: Discussionmentioning
confidence: 99%